Castor: A Renewed Oil Crop for the Mediterranean Environment - Valeria Cafaro; Giorgio Testa; Cristina Patanè (Agronomy, 2025)
Castor (Ricinus communis L.) is a plant belonging to the Euphorbiaceae family originated from Asia or Africa and well adapted to the Mediterranean environment. As an oilseed crop with a high oil content (35–65%), it is nowadays used for biofuels production, with a large potential for applications in chemical and pharmaceutical sectors as well. As for other oilseed crops, the interest towards this crop has grown exponentially in the past decades because of the necessity of limiting fossil fuels, obtaining clean energy, and use of a renewable energy source as required by RED (Renewable Energy Directive) within the European Union. Moreover, castor has a great adaptability in different soil and climate conditions, and it is known as a low-key maintenance crop. These characteristics, together with the necessity of increasing renewable energy sources, with the possibility of re-evaluating marginal lands, make castor the ideal plant to be exploited in the years to come. This review aims at giving useful information regarding its cultivation and soil and climate requirements, providing an overview on its spread on the market.